Diagnostic and therapeutic management of vesico‐ureteral reflux in pediatric kidney transplantation—Results of an online survey on behalf of the European Society for Paediatric Nephrology. (7th December 2022) - Zirngibl, Matthias; Buder, Kathrin; Luithle, Tobias; Tönshoff, Burkhard; Weitz, Marcus; ,
Abstract: Background: Vesico‐ureteral reflux (VUR) is considered to be a risk factor for recurrent febrile urinary tract infections and impaired renal transplant survival. Methods: An online survey supported by the European Society for Paediatric Nephrology was designed to evaluate current management strategies of VUR in native and transplanted kidneys of recipients aged <18 years. Results: Seventy‐three pediatric transplant centers from 32 countries contributed to the survey. All centers performed urological evaluation prior to pediatric kidney transplantation (KTx) with subsequent interdisciplinary discussion. Screening for VUR in native kidneys (30% in all, 70% in selected patients) led to surgical intervention in 78% (11% in all, 89% in selected patients) with a decided preference of endoscopic intervention over ureterocystoneostomy. Following KTx, continuous antibiotic prophylaxis was applied in 65% of the patients and screening for allograft VUR performed in 93% of selected patients. The main management strategies of symptomatic allograft VUR were continuous antibiotic prophylaxis (83%) and surgical treatment (74%) (endoscopic intervention 55%, redo ureterocystoneostomy 26%). Conclusions: This survey demonstrates the high variability in the management of VUR in pediatric KTx recipients, points to knowledge gaps, and might serve as a starting point for improving the care for patients with VUR in native and transplanted kidneys.